2020
DOI: 10.1186/s12875-020-01334-3
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of telephone triage in patients suspected of transient ischaemic attack or stroke: a cross-sectional study

Abstract: Background The Netherlands Triage Standard (NTS) is a widely used decision support tool for telephone triage at Dutch out-of-hours primary care services (OHS-PC), which, however, has never been validated against clinical outcomes. We aimed to determine the accuracy of the NTS urgency allocation for patients with neurological symptoms suggestive of a transient ischaemic attack (TIA) or stroke, with the clinical outcomes TIA, stroke, and other (neurologic) life-threatening events (LTEs) as the re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…A limitation was missing data on the final clinical outcome (35% of all relistened recordings). However, a previous detailed comparison in patient characteristics between those with a final diagnosis and those without showed that these groups were comparable (i.e., no indication of selection bias) (16). Therefore, we believe our results are generalizable to similar OHS-PC settings.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…A limitation was missing data on the final clinical outcome (35% of all relistened recordings). However, a previous detailed comparison in patient characteristics between those with a final diagnosis and those without showed that these groups were comparable (i.e., no indication of selection bias) (16). Therefore, we believe our results are generalizable to similar OHS-PC settings.…”
Section: Discussionsupporting
confidence: 51%
“…Neurological deficits may also be caused by multiple other (less urgent) disorders. Not surprisingly, the NTS decision support tool used in Dutch OHS-PC performs moderately regarding sensitivity and specificity in allocating adequate urgencies to patients with and without TIA/stroke (16). Literature on this topic is scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 It is also higher than the reported accuracy of telephone triage for patients with suspected cerebral vascular accidents. 18 Sensitivity of telephone triage was higher for outcomes at three and seven days (Supplementary Material 4), and sensitivity appeared to be increased at the expense of specificity in the later period of clinical assessment pathway implementation (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Different models for telephone triage in urgent and emergency care exist internationally. 18 32 33 NHS 111’s use of trained, non-clinical call advisors for initial assessment contrasts with other national triage services where assessments are performed by nurses and other clinicians. 33 As as been previously recommended, research is needed to determine the optimal configuration of such services in terms of accuracy and cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%